Pengaruh Literasi Data, Literasi Teknologi, dan Literasi Manusia terhadap Kesiapan Kerja Mahasiswa Prodi Pendidikan Bisnis di Era Revolusi Industri 4.0 - Difania Seftiaranisa Putri; Corry Yohana; Ivan Putranto (Indo Publishing, 2026)
This study aims to analyze the effects of data literacy, technology literacy, and human literacy on the work readiness of Business Education students in the era of the Fourth Industrial Revolution. This study employed a quantitative approach. The population consisted of 330 students from the 2023, 2024, and 2025 cohorts. The sample was selected using the proportional random sampling technique with the Slovin formula and a 5% margin of error, resulting in a total of 181 respondents. The questionnaire was distributed online and measured using a six-point Likert scale. Data analysis was conducted using Statistical Product and Service Solutions (SPSS) version 32. The results showed that data literacy had a positive and significant effect on the work readiness of Business Education students. Technology literacy had a positive and significant effect on the work readiness of Business Education students. Human literacy also had a positive and significant effect on the work readiness of Business Education students. Among the three independent variables, technology literacy had the most dominant effect on work readiness, as indicated by the t-test result, which showed a significance value of 0.0002 < 0.05. However, the R-squared value indicated that the independent variables simultaneously explained 53% of the variance in the dependent variable, suggesting that other factors outside the research model may also influence work readiness. These findings provide a theoretical implication that data literacy, technology literacy, and human literacy are factors that contribute to shaping students' work readiness in the era of the 4.0 Industrial Revolution.